A semi-automatic process for estimating fetus velocity using ultrasound imaging and videos - Mitrou, Michalis; Agrafiotis, Panagiotis; Georgopoulos, Andreas; Sideris, Apostolos (My University, 2015)
Contemporary technologies have positively affected everyday medical practice for the benefit of faster and more objective diagnoses. Image and video processing techniques have added potential to this effort, but still there is a long road ahead. In this paper a specially developed video processing methodology is described which determines the fetus velocity using B-mode ultrasonic video imaging. For that purpose, a semi-automated process using advanced computer vision and image processing tools is presented and evaluated. The results are presented with a detailed statistical analysis to verify the repeatability ad reliability of the method.
Keywords: Image segmentation; Models; Variational level